Utilización de granos secos de cervecería en la alimentación de vacas en producción en la quinta "Punzara" de la Universidad Nacional de Loja - López Cevallos, Jessenia Stefania (2018)
The present research work was carried out in the fifth experimental "Punzara" of the National University of Loja, with the purpose of contributing to improve the levels of milk production in Holstein cows, maintained in pasture, by using supplementary elaborations elaborated with different dry brewery inclusion levels (GSC). Four treatments were evaluated: T1 without GSC (control), T2 with 10% of GSC, T3 with 20% of GSC and T4 with 30% of GSC. Four Holstein cows with an average weight of 500 kg and an average production of 8.4 l / d were used, distributed according to a 4x4 Latin square design, with four treatments and four periods. The variables studied were: bromatological composition of the experimental rations; food consumption, milk production, milk quality, weight change and profitability. The results show an appreciable nutritional value of the rations prepared with GSC, with average values of 46.3% for dry matter; 16.2 and 24.3% for protein and crude fiber respectively. Food consumption was higher in treatment three with 14.37 kg / d; However, milk production showed no statistical difference between the treatments, with values of 7.7 to 8.4 l / cow / day; Likewise, the organoleptic characteristics and milk fat and protein content were not compromised and were close to the values reported by the literature for this breed. The weight of the animals did not show significant variations at the end of the experiment, with an average gain of 296 g / d. Finally, profitability was acceptable for all treatments; so it is concluded that the use of supplementary rations based on GSC, is a technically and economically viable alternative to improve milk production in the province of Loja. Keywords: Rations, milk production, milk quality, profitability.